AI in Canadian LIS Journals: A Text Analysis - Kroeker, Emily; Thornton, Gail M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2025)
Since its inception in 1955, the term “artificial intelligence” (AI) has seen a recent revival with generative AI. But what does this mean for Canadian Library and Information Sciences (LIS) responses? Text analysis was performed in 56 AI articles from nine Canadian LIS journals spanning 1982 to 2024. Using diachronic and sentiment trends, the identified corpus highlights that past familiarity with more traditional AI has led to a balanced and possibly more critical sentiment that provides context, acceptance, and concern for future generative AI technologies within the Canadian LIS landscape. L'IA dans les revues canadiennes de BSI: une analyse de texte Résumé Depuis sa création en 1955, le terme « intelligence artificielle » (IA) a connu un renouveau récent avec l'IA générative. Mais qu'est-ce que cela signifie pour les bibliothèques canadiennes ? Une analyse de texte a été effectuée sur 56 publications rédigées par l'IA, provenant de neuf revues canadiennes en BSI entre 1982 et 2024. En utilisant les tendances diachroniques et de sentiment, le corpus souligne que la familiarité passée avec l'IA plus traditionnelle a conduit à un sentiment équilibré et peut-être plus critique qui fournit contexte, acceptation et préoccupation pour les futures technologies en IA générative sur le plan canadien de la BSI. Mots-clés Intelligence artificielle; analyse de texte; contexte canadien